Can The IDX Be Hegded ? : Comparison of Black Scholes Option Model And Garch Option Model Using Long Strangle Strategy - Riko Hendrawan; Gede Teguh Laksana; Wiwin Aminah (Jurnal Manajemen Indonesia, 2020)
The purpose of this research was to compare the accuracy of the Black Scholes option model and the GARCH option model on index options using IDX Composite (IHSG) data from 2009-2018 with the long strangle strategy. The Black Scholes volatility constructed by using historical volatility, while GARCH volatility constructed by using the ARIMA model and the best lag. The accuracy of options analyzed using the average percentage mean square error (AMSE) to find the best model. The results of this study showed that for the one month option, the GARCH model is more accurate for a call option with 0.26%, while the Black Scholes model is more accurate for a put option with 0.18%. For the two month option, the GARCH model is more accurate for a call option with 0.92%, while the Black Scholes model is more accurate for a put option with 0.26%. For the three month option, the Black Scholes model is more accurate for a call option and put option with 2.00% and 0.31%, respectively. The results of this study further sharpen the research conducted by Bhat and Arekar (2016)and Hendrawan(2010) Keywords : Black Scholes Options Model; GARCH Option Model; Long Strangle; ,Index Option.,